Estudio de factibilidad de la creación de una empresa prestadora de servicios turísticos con destino al Valle del Cauca “MOLICIE TRAVEL” (2014)
This search try to show the viability of creating a company that provides travel services promoting the tourism within Valle del Cauca department, Molicie Travel has developed a portfolio considering the natural resources, the idea is to promote adventure, culture and ecology tourism, taking advantage of the diversity of our beautiful department. To determine the viability, we analyzed some factors such as political, economic, technological, demographic, social, cultural and its industrial sector as well, in this particular case will be the tourism industry, which is shown as a one of the most prosperous sectors in Colombia. Trying to define the administrative structure that we will use as a company management, first we will analyze a proposal for strategic direction, after this, the org chart will be present, where different functions that eventually will exist will be shown, both linked by a formal contract and as an outsourcing. In the legal analysis we can find the different steps that must be meeting to establish a legal business, according to Colombian law. Likewise Molicie Travel will inculcate to their customers a tourism friendly environment, encouraging the care and conservation of natural resources. Knowing the importance of a financial analysis for any project, an economic assessment is presented. It begins with the presentation of the investment costs for both the purchase of fixed assets and working capital financing, labor costs and fixed costs are presented as well. After performing this analysis we found the viability of establish a tourism service company, so initially will have three package tours in locations different locations with a variety of weather such as Buenaventura, La Union Valle and Lago Calima.